2017
DOI: 10.1016/j.psychsport.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Do web-based competitions promote physical activity? Randomized controlled trial

Abstract: for their assistance with data collection and Create IT for the development of the study website. Highlights  This study isolates the unique effect of competition on physical activity promotion  Competition increased physical activity relative to self-monitoring and control  Competition effects mediated by motivation (identified, intrinsic, importance)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 27 publications
0
39
0
1
Order By: Relevance
“…From a vote counting perspective, of 14 quantitative studies, 12 versus 2 [19,134] studies showed significant, positive effects of feedback on PA [17,55,77,86,89,120,122,123,127,129,133,135]. The remaining 18 studies reported qualitative, supporting results.…”
Section: Feedbackmentioning
confidence: 97%
See 3 more Smart Citations
“…From a vote counting perspective, of 14 quantitative studies, 12 versus 2 [19,134] studies showed significant, positive effects of feedback on PA [17,55,77,86,89,120,122,123,127,129,133,135]. The remaining 18 studies reported qualitative, supporting results.…”
Section: Feedbackmentioning
confidence: 97%
“…While studies used one or another form of feedback and PA and differed in methodological designs, using either more (e.g., descriptive pre-post comparison) or less systematic approaches (e.g., self-monitored changes in PA levels, interview results), the results generally indicated that feedback increased PA [18,126]. These qualitative findings were complemented by quantitative results that found a significant increase in PA in groups that received feedback compared with those that did not [17,55,86,89,120,122,123,129]. Despite these mostly positive effects, some qualitative studies also indicated there can be negative or null effects.…”
Section: Feedbackmentioning
confidence: 98%
See 2 more Smart Citations
“…In the time following the attainment of predetermined thresholds of sufficiency and stability for post‐intervention effects, we identified 23 further RCTs published to 2013. Although not included in the review, further intervention trials have been conducted and published since we ran our searches .…”
Section: Discussionmentioning
confidence: 99%